ANALISIS FENOMENA SOSIAL KUASA ELIT DI DUSUN JAMBU SLEMAN YOGYAKARTA - Dwi Listia Rika Tini; Nur Inna Alfiyah (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2022)
This research is to find out the basis of the power possessed so that the actors in sand mining are called elites. Besides that, it is also to find out the capacity of the elites and the relationship patterns that are run by these elites. The method used is an approach to collect data and analyze data, in the form of data collection through observation and interviews. While the data analysis uses the Miles and Huberman model, using phases, data reduction, data display, and conclusion drawing/verification. The results showed the elite stratification in sand mining in Jambu Hamlet, namely The Big Bourgeoisie/Upper Class consisting of land owners and equipment owners and local government at the highest level (provincial), The Petty Bourgeoise/ Middle Class consisting of Operators, Helpers, Managers, The foreman, the land owner community, the head of the coker group, the local government, the working class/lower class consisting of the coker and the community. However, judging from the capacity of the ruling elite, the existence of elite rulers is in the classification of the petty bourgeois ruling class or the middle class because managers as elite determinants and management decision making are extensions of entrepreneurs who have business interests. So that the pattern relationship shows the regularity of sand mining management which develops intensive communication between entrepreneurs and managers so that there is no visible conflict about results.